Citizen Language: Color and Accessibility - Paulo Carvalho, Luiz; Cappelli, Claudia; Santoro, Flávia (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
Colors make some aspects of business process models understandability easier. Although papers confirm this claim, they did not deal with color-blind people. Some notations even prohibit the use of colors. Accessibility studies have demonstrated safe colors, enabling wide understandability. This work proposes the use of safe colors for graphic processes represented in Citizen Languages, improving its mandatory transparency.